In vivo MRI biocompatibility evaluation of functionalized carbon fibers in reaction with soft tissues - Prokic, B.B.; Bacic, G.; Prokic, B.; Kalijadis, Ana; Todorovic, Vera; Puskas, Nela; Vidojevic, D.; Lausevic, Mila; Lausevic, Z. (Acta veterinaria (Beograd), 2012)
In modern medicine implants are very important and so is their design and choice of materials. Almost equally important is the choice of imaging technique used to in vivo monitor their fate and biocompatibility. The aim of this study was to evaluate the ability of magnetic resonance imaging (MRI) in monitoring the biocompatibility of two newly designed carbon fibers. We have analyzed the interaction of surface functionalized carbon fibers (basic and acidic) with muscle and subcutaneous tissues of rabbits. MRI techniques showed to be useful in longitudinal monitoring of the surrounding tissues, assessment of biocompatibility of new implants, and in the distinction of in vivo surgical edema from inflammation. Histopathology confirmed MRI results, thus showing that MRI has a great potential for in vivo studies of such materials. [Projekat Ministarstva nauke Republike Srbije, br. III 45006 and III 41005]